Síndrome da fragilidade e fatores associados em idosos comunitários do município de Santa Cruz RN - Sousa, Ana Carolina Patrício de Albuquerque (2010)
The frailty in the elderly is characterized by decreased physiological reserves, and is associated with increased risk of disability and high vulnerability to morbidity and mortality. This study is part of a multicentric project on Frailty in Elderly Brazilians (REDE FIBRA). Aims: to investigate characteristics, prevalence and associated factors related to frailty. Metodology: We interviewed 391 elderly patients aged 65 years, selected randomly. Data collection was performed using a multidimensional questionnaire containing information about socio-demographic and clinical variables. To characterize the frail elderly, was considered the phenotype proposed by Fried. Data were analyzed using descriptive statistics, bivariate analysis (χ ²) and binary logistic regression. Results: The prevalence of frailty was 17.1%. In the final model of multivariate analysis, was obtained as factors associated with frailty: advanced chronological age (p <0.001), have comorbidity (p <0.035), show dependence on performing basic activities of daily living (p <0.010) and instrumental (p <0.003) and have poor perception of health status (p <0030). Conclusions: The factors associated with frailty suggest a predictive model helping to understand the syndrome, guiding actions that minimize adverse effects on the aging process